The Kaiser : new research on Wilhelm II's role in imperial Germany - Mombauer, Annika; Deist, Wilhelm (Cambridge University Press, 2003)
This book examines the role of Germany's last emperor, Wilhelm II, focusing on the final years of his reign (1900-1918). The essays highlight Wilhelm's importance from a number of different foreign and domestic angles, and are based on the very latest research on Wilhelmine Germany.